Transport outlook 2009: Globalisation, crisis and transport - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
This second ITF Transport Outlook continues building towards a full-fledged Transport Outlook, building upon the first Outlook (JTRC, 20081). The 2008 Outlook investigated the relation between expected GDP evolution and the demand for road transport, pointing out that transport demand and CO2-emissions could well turn out higher than commonly assumed given the projected evolution of GDP, and underlining the potential of improvements of fuel efficiency in controlling CO2-emissions from road transport. These topics were developed further in the '50 by 50 Global Fuel Economy Initiative'.2 The 2009 Outlook considers two themes that are closely linked to the International Transport Forums's them for the 2009 meeting in Leipzig: Transport for a global economy - Challenges and opporturnities in the downturn. First, in Section 2, we focus on the evolution of GDP itself and how this evolution interacts with transport demand and investments in transport infrastructure. The analysis is a first brush at gauging the potential impacts of the economic and financial crisis. Specifically, we consider (a) the impact of the aggregate demand shock on the evolution of global GDP, (b) the need and potential for a rebalancing of global growth patterns, with their implications for trade and transport demand, and (c) the consequences of the widening funding gap for transport infrastructure investments. Second, in Sections 3 through 5, we discuss projections of the demand for road transport, aviation, and maritime transport. For road transport, more modest global growth leads to slower growth of the vehicle stock and of CO2-emissions, but the basic messages of the 2008 Outlook continue to hold. For aviation, we attempt to disentangle the effects of economic growth and of increased openness of markets on volume growth, and find that the latter is an important growth factor. For maritime transport, the focus is on likely development patterns and how they could be affected by the crisis, and how this does (not) affect recommendations for dealing with expected CO2-emissions.
Keywords: 330